CYBER EXTENTION AS AN ALTERNATIVE INNOVATION OF CEREBRAL PALSY FAMILY COMMUNICATION NETWORK - Nurul Bahriyah, Euis; Muharul Tambunan, Resman; A Faaroek, Safiani; Istambul, Rozahi (International Journal of Psychosocial Rehabilitation, 2020)
One of the problems of the family of cerebral palsy teenagers is that they still need a lot of information systematically and scientifically through counseling in order to build psychological functions of the families of cerebral palsy teenagers so that all family members can function fully to provide resilience for the care of cerebral palsy teenagers to fully help their children has limitations. One form of building resilience in parenting adolescent cerebral palsy is providing interventions in the form of counseling and information sharing through discussions and gatherings of several parents of cerebral palsy children who are then formed into communities that share information, share feelings, strengthen each other, remind each other, care for each other so that parenting of their cerebral palsy teenagers becomes lighter and easier. One of the communication media that support the resilience of cerebral palsy adolescent care is to utilize cyber extensions which are new innovative communication media that are hybrid and convergent that utilize internet and interactive multimedia networks to bridge the process of information and knowledge transformation in the care and development of cerebral palsy teenagers. . So it is no longer a barrier to geographical distance between therapists, communities, families of urban cerebral palsy teenagers and families of cerebral palsy teenagers in different areas. The method used in this research is descriptive method, namely research that aims to describe and explain things as they are, while the materials and methods used in this study use literature studies (literature review). The conclusion of this study is the optimization of the cyber extension as an alternative communication network innovation for families of cerebral palsy adolescents in resilience and growth and development of adolescent palsy by the use of computer information technology in terms of sharing information with fellow families of cerebral palsy children both in the form of community and therapist counseling. or medical rehab doctor through the internet one of them with social media.